Books Completed or in Process by Academy Members (Academy of Management Journal, 1963)
A list of books relating to management is presented. They include “Management Thought in a Dynamic Economy,” by John F. Mee, “New Horizons in Decision-Making,” by E. J. Forsythe and Palmer G. Pilcher, and “Fundamentals of Industrial Management,” by Alfred Bornemann.